JOB SATISFACTION AND INTERPERSONAL RELATION: A DETERMINANT OF JOB PERFORMANCE OF ACADEMIC STAFF OF COLLEGES OF EDUCATION IN LAGOS STATE, NIGERIA - Modupe Bosede Lewis; Busuyi Francis Olowo; Comfort Abosede Okotoni (Sanata Dharma University Yogyakarta, 2020)
This study investigated the level of job satisfaction among the academic staff in colleges of education in Lagos State. It evaluated the level of interpersonal relations that existed between the academic staff and the students and also ascertained the level of interpersonal relations that existed between the staff and the management of the institutions. Quantitative approach with survey design was used for the study. Population for the study comprised 516 academic staff and 6042 students of all the colleges of education in Lagos State. Sample for the study comprised 51 lecturers and 604 students, a total of 655 respondents were selected from one federal-owned college of education, one state-owned college of education and one private-owned college of education within Lagos State. The sample was selected using multistage sampling procedure. Two research instruments were used for the study, namely: Determinants of Job Performance Questionnaire (DJPQ) and Students’ Rating on Job Performance Questionnaire (SRJQ). Data were analysed using percentage and ANOVA statistics at 0.05level of significance. The results showed that there was a high level of job satisfaction among the academic staff of the colleges of education in Lagos State (58%) and that there was a moderate level of interpersonal relations between the academic staff and the students (69.7%).